Chemical Characterisation-Biological Evaluation of Greek Cultivar Cardoon Seeds (Cynara cardunculus). A By-product with Potential High Added Value - Graikou, Konstantia; Kourti, Panagiota-Maria; Zengin, Gokhan; Gortzi, Olga; Danalatos, Nikolaos; Chinou, Ioanna (Planta Medica, 2021)
Cynara cardunculus (artichoke) is a perennial plant of the Mediterranean basin, known since antiquity as food and for its therapeutic properties. Cynara is a relatively small genus with two cultivated species and one wild one. Recently, successful efforts have been made to cultivate wild cardoon and monetise it as a bioenergy crop. In this study, the seeds of an established Greek cultivar of C. cardunculus, cultivated in the experimental field and used as biofuel, have been researched for their chemical profile and nutritional value. According to the results, six lignans were isolated [arctigenin, arctiin, trachelogenin, tracheloside, cynarinine, and ethylate of trachelogenin (isolated for the first time from a natural source)] as well as the most characteristic metabolites of the genus (linoleic acid, trilinolein, and 3,5-dicaffeoylquinic acid). Moreover, the total phenolic content (31.18 – 54.51 mg gallic acid equivalents/g extract) and antioxidant and enzyme inhibitory activities of the seeds have been evaluated and showed strong antioxidant properties (44.42 – 516.81 mg gallic acid equivalents/g extract) as well as satisfactory bleaching (enzyme tyrosinase, 16.95 – 23.80 mg kojic acid equivalents/g extract), antidiabetic (enzymes a-amylase, a-glucosidase, 0.14 – 1.75 mmol acarbose equivalents/g extract), and protective against neurodegenerative disease (cholinesterase enzymes, 0.49 – 1.22 mg galanthamine equivalents/g extract) activities. The nutritional evaluation of the seeds confirmed them as a rich source of unsaturated fatty acids, dietary fibre (24.1%), and high protein content (19.3%). It is noteworthy that such a neglected bioactive by-product, with essentially high nutritional value, as the studied seeds could be investigated for its value-added applications towards food and food supplements areas.
Keywords: Cynara cardunculus Greek hybrid; Asteraceae; lignans; biological evaluation; nutritional value